Facial Pain Associated with CPAP Use: Intra-Sinusal Third Molar. (5th June 2014) - Mermod, Maxime; Broome, Martin; Hoarau, Remy; Zweifel, Daniel
Abstract : Objective . This paper describes a patient with left hemifacial pain elicited by the use of a CPAP mask. Case Report . A 74-year-old man was referred with a history of pain in the left maxillary sinus related to the use of his CPAP interface, thereby prohibiting the use of the latter. Computed tomography revealed an intra-sinusal ectopic third molar in the left maxillary sinus floor corresponding to the painful area. After removal of the ectopic tooth under local anesthesia by a Caldwell-Luc approach, the patient was relieved of his symptoms. Conclusion . Although an ectopic tooth in the maxillary sinus is rare, this case points out the importance of actively looking for a regional problem if patients cannot tolerate the CPAP interface since this can lead to issues of incompliance and medical complications due to the untreated obstructive sleep apnoea syndrome.